Recent Advances in the Syntheses of Amines with the Leuckart Reaction - Umar , Q.; Luo , M. (Novel Aspects on Chemistry and Biochemistry Vol. 5, 2023)
This chapter presents a summary of reactions classified as “Leuckart-type reactions”. The aim of the chapter is to discuss the significance as well as recent advancements in the syntheses of amines via simple and inexpensive methods using readily available raw materials. This review includes all catalytic and noncatalytic reactions that involve the Leuckart method. Recent research revealed that reductive amination was used in at least 25% of the C–N bond-forming reactions used in the pharmaceutical sector. Recent improvements of the experimental methods have provided exceptional yields. There are two types of “Leuckart reactions”, including indirect reductive amination, in which an imine is prepared from the carbonyl compound and amine and reduced with a suitable reducing agent to obtain the “corresponding amine” (“Scheme 1a”), and “direct reductive amination” (“Scheme 1b”) or “one-pot reactions”. Eschweiler-Clarke methylation is theoretically related to the "Leuckart-type reaction". According to the principles of action, substances are categorized as those that affect the central nervous system, the cardiovascular system, or the gastrointestinal tract, anticancer medications, antibiotics, antiviral and antifungal medications, drugs that treat anxiety, convulsants, biotics, HIV medications, and antidiabetic medications. Therefore, this contribution reviews Leuckart preparations of nitrogenous compounds as well as their use in other areas of human development.